2015
DOI: 10.1177/1526602815592133
|View full text |Cite
|
Sign up to set email alerts
|

Laser Atherectomy for Treatment of Femoropopliteal In-Stent Restenosis

Abstract: When used to treat complex ISR, including in-stent occlusions, laser atherectomy with adjunctive balloon angioplasty may be associated with improved patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Armstrong et al 16 confirmed prior observations that operators appear to select the laser for longer (222 vs 114 mm) and more complex lesions (total occlusions 69% vs 20%) than BA, respectively. Shammas et al 27 noted the same when laser was compared with SilverHawk (Medtronic CardioVascular, Santa Rosa, CA, USA) for treating femoropopliteal ISR.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Armstrong et al 16 confirmed prior observations that operators appear to select the laser for longer (222 vs 114 mm) and more complex lesions (total occlusions 69% vs 20%) than BA, respectively. Shammas et al 27 noted the same when laser was compared with SilverHawk (Medtronic CardioVascular, Santa Rosa, CA, USA) for treating femoropopliteal ISR.…”
supporting
confidence: 56%
“…The problems with stenting the femoropopliteal segment are well illustrated by Armstrong et al 16 in this issue of the JEVT. In this "real world" retrospective study, stent fractures at index were observed in 10% to 11% of patients.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In a recent report, Milnerowicz et al studied the combination of RA + DCB for the treatment of iliac and infrainguinal in‐stent occlusions and achieved a 12‐month freedom from restenosis rate of 79.5% and 12‐month freedom from TLR 94.5% . LA helps debulk the neointimal tissue from the restenosed stent and therefore decreases recoil before balloon inflation . At the same time, by offering plaque modification and creating micropores, it may facilitate paclitaxel uptake and retention in the lesion .…”
Section: Discussionmentioning
confidence: 99%
“…32 Apart from our group, LA in combination with DCB has been studied also in a single-center RCT by Gandini et al 36 LA helps debulk the neointimal tissue from the restenosed stent and therefore decreases recoil before balloon inflation. 37 At the same time, by offering plaque modification and creating micropores, it may facilitate paclitaxel uptake and retention in the lesion. 7,[38][39][40] As a result, LA and DCB likely have synergistic effects.…”
Section: Discussionmentioning
confidence: 99%